Portraits of Labor Market Exclusion 2.0 : Country Policy Paper for Croatia - Ovadiya, Mirey; Vandeninden, Frieda (World Bank, Washington, DC, 2018)
This report is a joint study between the European Commission (EC), the World Bank, and the Organization for Economic Cooperation and Development (OECD). It aims to inform employment support, activation, and social inclusion policy making, through an improved understanding of labor-market barriers. Covering 12 countries, the study builds on the previous joint EC and World Bank study to map the diversity of profiles of individuals who are out of work in six countries (Sundaram et al., 2014) and other analyses that characterize individuals with labor market difficulties (European Commission, 2012; Ferré et al., 2013; Immervoll, 2013). The study expands the previous analysis by looking at a broader group of labor market vulnerable beyond the out of work individuals to include: those in unstable employment, those with restricted hours, and those with near-zero incomes (i.e. individuals who are marginally employed). It also refines the analytical methodology by applying an employment barriers framework to facilitate policy making and country-specific application, and to provide a reference point for future methodological extensions.